The out-of-sample forecasting performance of variable parameter exchange rate models in South Africa - Gilbert Wesso (South African Journal of Business Management, 1995)
In this article the out-of-sample forecasting performance of exchange rate determination is examined without imposing the restriction that coefficients are fixed over time. Both fixed and variable coefficient versions of conventional structural models are considered, with and without a lagged dependent variable. A Variable Parameter Regression (VPR) technique based on recursive application of the Kalman filter is used to improve the predictive performance of a class oi monetary exchange rate models.
Keywords: 650